2007
DOI: 10.1158/1055-9965.epi-06-0588
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Negatively Associated with Prostate-Specific Antigen in U.S. Men, 2001-2004

Abstract: Background: Recent studies have shown a negative association between body mass index (BMI) and prostate-specific antigen (PSA), a commonly used serum marker for the detection and diagnosis of prostate cancer. We have examined the association between several anthropometric measures and PSA in a nationally representative sample of men. Methods: We analyzed data from the 2001-2004 National Health and Nutrition Examination Survey. Participants in this study were men ages z40 years without previously diagnosed pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
104
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 46 publications
12
104
3
Order By: Relevance
“…8,9,11 These findings were also confirmed by our study. Interestingly we did not find any statistically significant association between PSA and the use of NSAIDs, statins or thiazide diuretics as found by Chang et al 7 Different ways of defining smoking status, and various sociodemographic, clinical factors and medications examined in these 2 studies may partially account for this difference.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…8,9,11 These findings were also confirmed by our study. Interestingly we did not find any statistically significant association between PSA and the use of NSAIDs, statins or thiazide diuretics as found by Chang et al 7 Different ways of defining smoking status, and various sociodemographic, clinical factors and medications examined in these 2 studies may partially account for this difference.…”
Section: Discussionsupporting
confidence: 87%
“…5,6 Epidemiological studies have also shown that PSA can be affected by several heath characteristics including obesity, diabetes and certain medications such as NSAIDs, statins and thiazide diuretics. [7][8][9] Scant data exist on the association between smoking and PSA levels. Gelmann et al reported that current and former smokers had a statistically significantly lower PSA and fPSA levels compared with never smokers.…”
mentioning
confidence: 99%
“…The results of our study suggested that a relevant reduction in PSA might be restricted to obese men (À14%), which in part might be attributable to the effect of hemodilution (30). The PSA reduction was comparable with the reduction found in previous studies: À9% to À19% (2,3,6,8,31). Likewise, the risk of localized prostate cancer was reduced in obese compared with normal-weight men (À8%, when assuming a BMI difference of 10 kg/m 2 ) according to the metaanalyses of MacInnis et al (32).…”
Section: Discussionsupporting
confidence: 84%
“…Whether or not there was any difference in genetic background or dietary lifestyle between the Japanese patients in our study and the Korean patients in the previous study 18 remains unclear. Both population-based studies 26,27 and studies of patients with clinically localized PCa treated by RP 5 have found that obese men have lower PSA levels compared with nonobese men. Hemodilution and low androgenic activity are reported to have an inverse relationship with obesity and serum PSA levels.…”
Section: Discussionmentioning
confidence: 99%